(untitled) (Ameghiniana, 2025)
The Sparassodonta were the dominant mammalian predators in South America during much of the Cenozoic. Among them, Thylacosmilus atrox, with its hyperdeveloped upper canines and bizarre anatomy, has drawn considerable attention. This study investigates infraorbital foramen (IOF) size and its implications for the paleoecology of sparassodonts, focusing on Thylacosmilus. Using computed tomography (CT), micro-computed tomography (μCT), and comparative analyses, we examined the relationship between IOF area (IOFarea) and certain anatomical correlates, including foramen rotundum area (FRarea), several endocranial structures, and skull dimensions. Comparisons were made within Sparassodonta and to marsupials and carnivorans. Our results reveal that greater variation in IOFarea exists among sparassodonts compared to marsupials, with some large borhyaenoids exhibiting disproportionally large IOFarea. Notably, Thylacosmilus displays intrataxon variation in IOFarea. Contrary to previous studies, which stated that Thylacosmilus possessed a relatively small IOF that might have been consistent with scavenging behavior, our findings indicate that IOFarea in Thylacosmilus does not substantially differ from that of the active predators in our sample. This study highlights the anatomical diversity of IOF in sparassodonts and underscores the complexity of making behavioral inferences from partial cranial morphology.